Pandangan Sahl al-Tustarī terhadap Al-Qur’an dalam Tafsīr Al-Qur’ān al-’Aẓīm - Ahmad Ali Fikri; Yusuf Rahman (Refleksi: Jurnal Kajian Agama dan Filsafat, 2023)
This article examines the views of Sahl al-Tustarī on the Qur’an. As the first Sufi Mufasir who write a Sufi commentary of the Qur’an, al-Tustarī has laid down the principles of Sufistic interpretation of the Qur’an. This research is a library study that its data is based on written sources. The main source of this research is Tafsīr al-Qur’an al-’Aẓīm by Sahl al-Tustarī. The research approach used is a structural approach initiated by Robert Scholes with an interpretive and comparative framework. This paper shows that among al-Tustarī’s views on the Qur’an which are important and the basis for his Sufistic interpretation is that the Qur’an is an Arabic holy book and has four levels of meaning; ẓāhir, bāṭin. ḥadd and maṭla’.